High-frequency modulation of oxide-confined vertical cavity surface emitting lasers - Geib, K. M., author; Schneider, R. P., author; Kilcoyne, S. P., author; Choquette, K. D., author; Mar, A., author; Lear, Kevin L., author; IEE, publisher (Colorado State University. Libraries, 1996)
High-speed studies of packaged, submilliampere threshold, oxide-confined vertical cavity surface emitting lasers show modulation bandwidths > 16GHz. Very high modulation current efficiency factors occur at low bias but decrease as the modulation bandwidth and frequency of the relative intensity noise peak saturate at higher currents.
Keywords: vertical cavity surface emitting lasers; semiconductor junction lasers; optical modulation